2010
DOI: 10.1016/j.physletb.2010.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Analytical approach for the approximate solution of the longitudinal structure function with respect to the GLR-MQ equation at small x

Abstract: We show that the nonlinear corrections to the longitudinal structure function can be tamed the singularity behavior at low x values, with respect to GLR-MQ equations. This approach can determined the shadowing longitudinal structure function based on the shadowing corrections to the gluon and singlet quark structure functions. Comparing our results with HERA data show that at very low x this behavior completely tamed by these corrections.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…The inverse Laplace transform of brackets in Eqs. (6) and (7) are defined as kernels Egi and Esi (i=1 and 2) respectively. We firstly refer to the ν-space as Ef i(ν, t)≡L −1 [[....]; ν] (f = g, s) then define ν≡ ln(1/x).…”
Section: Formulism Decoupling Dglapmentioning
confidence: 99%
See 1 more Smart Citation
“…The inverse Laplace transform of brackets in Eqs. (6) and (7) are defined as kernels Egi and Esi (i=1 and 2) respectively. We firstly refer to the ν-space as Ef i(ν, t)≡L −1 [[....]; ν] (f = g, s) then define ν≡ ln(1/x).…”
Section: Formulism Decoupling Dglapmentioning
confidence: 99%
“…These nonlinear corrections have been calculated by Gribov, Levin,Ryskin, Mueller and Qiu (GLR-MQ) [5] and tame the parton distributions behavior at sufficiently low x. In recent years [6][7], the Regge-like behavior for the gluon density used in the GLR-MQ equation. The key ingredient is the gluon behavior in this region, especially the effect of screening on the Regee trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies of the GLR-MQ equation in the framework of extracting the PDF, of the free proton is given in Refs. [42][43][44].Various studies in the solutions and viable generalisations of the GLR-MQ equation have been reported in recent years [42,45].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we consider the range x ≥ 10 −3 . We expect that at low initial scale the DGLAP evolution with a leading twist is not sufficient at low x [93,94] and one needs to consider the higher twist corrections in the DGLAP equation [95][96][97][98][99][100][101]. It should be mentioned here that there is also uncertainty from the longitudinal basis resolution within the initial scale PDFs.…”
Section: B Qcd Evolution Of Heavy Meson Pdfsmentioning
confidence: 98%